G175(P) Current dilution methods cause large variations and inaccuracies when making up 1MCG synacthen dose. (24th May 2017) - Cross, AS; Sachdev, P; Wright, NP; Jabbar, I; Elder, CJ
Abstract : Aims: The low-dose Short Synacthen test is a popular diagnostic test of adrenal insufficiency in children. It is employed by 82% of UK paediatric endocrinologists. Although various dosing strategies exist, 1 mcg is most commonly employed, however none of the low-dose forms of Synacthen are commercially available. A 'British Society for Paediatric Endocrinology and Diabetes' survey revealed 14 different methods for diluting 250 mcg/ml ampoules. We investigated whether the various dilution strategies result in differences in the resultant Synacthen dose administered. Methods: The ten most popular dilution methods were tested, encompassing different diluents (0.9% saline n=9, 5% dextrose n=1), single (n=6) and double (n=4) dilution strategies and varying initial quantities of Synacthen (0.1 to 1 ml). Each method was made up five times under simulated ward conditions and three samples were taken from different parts of the bag of resultant solution. Samples were frozen then batch-analysed on an hACTH radioimmunoassay validated for Synacthen. All samples were diluted to 250 pg/ml (most sensitive part of the assay measuring range) and the coefficient of variation (CV) calculated. Results: There was marked variation in Synacthen detected from the three samples taken from the same solution (CV 13.4%– 194.6%) suggesting inadequate mixing, the five preparations of the same method, suggesting batch to batch variation, and between the ten different preparation methods (CV range 24.2%–163.7%) suggesting divergence between methods. Estimates of the likely Synacthen dose, if administered to patients, ranged from less than 0.04 mcg to more than 2 mcg. Conclusion: Considerable variation was observed both within and between dilution methods. Variables, which may affect the actual dose of Synacthen administered, include: poor dilution technique, inappropriate dilution strategies, pharmaceutical manufacturer variation, use of inaccurate ward equipment, volume inconsistencies, lack of adequate mixing and lack of a controlled environment. We recommend low-dose Synacthen be made up under laboratory conditions and call for a commercial preparation of 1 mcg Synacthen.